Analysis of propagation of orthogonally polarized supermode in straight and curved multicore microstructured fibres - A. Goncharenko, Igor; Marciniak, Marian (Journal of Telecommunications and Information Technology, 2007)
We analyze the dependence of radiation loss, effective indices and difference of the effective indices of the two modes with similar field distribution propagating in dual-core microstructured fibres as well as their polarization behavior on fibre parameters (air hole diameter, hole separation, distance between guiding cores) and fibre bending. Optimization of the parameters of such fibres using as vector bend sensors is considered.
Keywords: multicore fibre; microstructured fibre; upermode; birefringence; mode dispersion; method of lines